Nonglom Wetlands management planning - Mam, Kosal (2024)
The Nonglom wetlands are located in the agricultural landscape of Samakhixay, where resources such as water, land, and fish have been heavily exploited to support local livelihoods. Currently, there are few, if any, management actions in place to regulate resource access and use, let alone efforts to restore or re-establish the wetland ecosystem functions and the goods and services provided by the once natural habitats. The purpose of the wetlands governance and management innovation is to restore, as much as possible, the wetland ecosystem functions—such as water provision, water purification, and habitats for biodiversity, fish, and other wildlife—along with their associated goods and services. This will be achieved through the application of relevant agroecological principles and the re-establishment of the area’s natural habitats. This initiative will also provide a roadmap and springboard for realizing other proposed innovations for agroecological transitions. The research question for this innovation is: How do agroecological innovations perform in restoring wetland ecosystem functions across the landscape, and how should they be adapted to the local context.